Ice hockey skate starts: a comparison of high and low calibre skaters - Renaud, P. J.; Robbins, S. M. K.; Dixon, P. C.; Shell, J. R.; Turcotte, R. A.; Pearsall, D. J. (Sports Engineering, 2017)
The forward skating start is a fundamental skill for ice hockey players, yet extremely challenging given the low traction of the ice surface. The technique for maximum skating acceleration of the body is not well understood. The aim of this study was to evaluate kinematic ice hockey skating start movement technique in relation to a skater`s skill level. A 10-camera motion capture system placed on the ice surface recorded "hybrid-V" skate start movement patterns of high and low calibre male ice hockey players (n = 7, 8, respectively). Participants` lower body kinematics and estimated body centre of mass (CoM) movement during the first four steps were calculated. Both skate groups had similar lower body strength profiles, yet high calibre skaters achieved greater velocity; skating technique differences most likely explained the performance differences between the groups. Unlike over ground sprint start technique, skating starts showed greater concurrent hip abduction, external rotation and extension, presumably for ideal blade-to-ice push-off orientation for propulsion. Initial analysis revealed similar hip, knee and ankle joint gross movement patterns across skaters, however, further scrutiny of the data revealed that high calibre skaters achieved greater vertical CoM acceleration during each step that in turn allowed greater horizontal traction, forward propulsion, lower double-support times and, accordingly, faster starts with higher stride rates.